Optimalisasi Bimbingan Konseling Untuk Meningkatkan Kualitas Belajar Terhadap Perilaku Siswa Di SMAS Al-Azhar Medan - Nur Fadillah Butar-Butar; Alifia Azizah Ilmi; Ade Bagus Suponco; Ahmad Anas Hasibuan; Fauziah Nasution (Institut Nalanda, 2023)
Schools in essence have a significant role in shaping the character and moral behavior of children who have good character. Schools also have a significant role in providing education and defense for children to be free from the negative bondage of the growth of globalization which is marked by rapid advances in the field of data and communication technology. So that in the process of teaching and learning between teachers and students it is necessary to have an approach both physically and mentally, moreover the teacher as someone who has knowledge who wants to share his knowledge with students must understand very well what are the attitudes and characteristics of the students who want to be educated by the teacher. There are many methods that can be tried so that a teacher as a teaching staff has integrity, synergizes and is like a role model in carrying out teaching to students, step by step, step by step can be learned so that a teacher can master the attitudes and characteristics of their students so that they can make their students capable. master the knowledge that the teacher wants to impart. Each student can be determined to have very heterogeneous attitudes and characteristics